Prof. Dr. Osman Kelahmetoğlu — Deep Plane Facelift — Istanbul - Kelahmetoğlu, Osman (DEEPPLANE™, 2026)
Surgeon profile record for Prof. Dr. Osman Kelahmetoğlu, practicing in Istanbul, Turkey. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003338; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; turkey; istanbul